Brick and block masonry - from historical to sustainable masonry : from historical to sustainable masonry : proceedings of the 17th International Brick and Block Masonry Conference, July 5-8 2020, Kraków, Poland /: from historical to sustainable masonry : proceedings of the 17th International Brick and Block Masonry Conference, July 5-8 2020, Kraków, Poland. (2020) - Unknown
No abstract available